Numerical investigations of the convergence of a remeshing algorithm on an example of subsonic flow - Kucwaj, J. (Computer Assisted Methods in Engineering and Science, 2010)
The main goal of the paper is to analyze convergence of a remeshing scheme evaluated by the author [8] on the example of a potential flow around a profile. It is assumed that flow is stationary, irrotational, inviscid and compressible. The problem is led to solving nonlinear differential equation with additional nonlinear algebraic equation representing the so called Kutta-Joukovsky condition. For adaptation a remeshing scheme is applied. For every adaptation step mesh is generated using grid generator [7], which generates meshes with mesh size function. The mesh size function is modified at every adaptation step by nodal values of the error indicator interpolation. The nonlinear algebraic system of equations obtained from discretizing of the problem, is solved by the application of the Newton-Raphson method.